Effect of MgO Grade in MgO–C Refractories on the Non‐metallic Inclusion Population in Al‐Treated Steel. Issue 6 (31st May 2022) - Kerber, Florian; Zienert, Tilo; Hubálková, Jana; Stein, Volker; Schemmel, Thomas; Jansen, Helge; Aneziris, Christos G.
Abstract : In article 2100482, Kerber and co‐workers show the immersion of a MgO‐C refractory specimen into molten steel performed in a steel casting simulator. The solidified steel is analyzed regarding the inclusion population via an automated feature analysis. Different species of inclusion are observed. The element mapping of a multi‐phase inclusion is shown on the left side of the cover image.